(-3)(2x-5)-8=7-x

Simple and best practice solution for (-3)(2x-5)-8=7-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3)(2x-5)-8=7-x equation:


Simplifying
(-3)(2x + -5) + -8 = 7 + -1x

Reorder the terms:
-3(-5 + 2x) + -8 = 7 + -1x
(-5 * -3 + 2x * -3) + -8 = 7 + -1x
(15 + -6x) + -8 = 7 + -1x

Reorder the terms:
15 + -8 + -6x = 7 + -1x

Combine like terms: 15 + -8 = 7
7 + -6x = 7 + -1x

Add '-7' to each side of the equation.
7 + -7 + -6x = 7 + -7 + -1x

Combine like terms: 7 + -7 = 0
0 + -6x = 7 + -7 + -1x
-6x = 7 + -7 + -1x

Combine like terms: 7 + -7 = 0
-6x = 0 + -1x
-6x = -1x

Solving
-6x = -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-6x + x = -1x + x

Combine like terms: -6x + x = -5x
-5x = -1x + x

Combine like terms: -1x + x = 0
-5x = 0

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| 20-0.5x=21 | | 4b-6-12b-5= | | (x-3)(x-3)=36 | | 4(u-6)+3u=32 | | 6(7a-1)=8(4a+11) | | 14=7x+4-2x | | 7x-(5x+13)= | | 3f+10f=26 | | x^2+64-225=0 | | a-8s=8(9-st) | | y=-0.6x+4 | | -8y+2(y+6)=18 | | 30=6a+12 | | 0=(2x^2)-16 | | 29-7x=17+5x | | x+35=-7x-35 | | -3.3=x+(-1.1) | | -6z-4=-10 | | 40c-.05(40c)=190 | | -4.9x^2+100x=0 | | 4w-15w=33 | | 3y+2a=3y-10 | | 0.5(8x-8)=4x+8 | | 5(3+x)-x=4(x+2)+7 | | 2(2x-30)=90 | | [2(14-7)-28]= | | 5y-5=120 | | 4w-15=33 | | -13-x=-3x+5 | | 7m+3=-18 | | 84=x-5(6+4x) | | 5+6=10+2 |

Equations solver categories